PENGEMBANGAN BAHAN AJAR ELEKTRONIK BERBASIS MOBILE-LEARNING PADA MATA KULIAH OPTIK DI FKIP UNIVERSITAS JEMBER - Rifati Dina Handayani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
In this global and modern era, the interaction between a teacher and students still could be done after teaching and learning process in the classroom because of the development of information technology. This research was aimed to to design electronic teaching materials based Mobile-Learning (M-Learning). This teaching material was designed by using the 4D Model which was reducted to become 3D: Define, Design, and Develop. The target of doing this research was electronic teaching materials based Mobile-Learning (M-Learning) at “Optik” (Optics) subject. This teaching material was presented by using electronic medium such as phonecell or tablet because they were very easy to bring whenever and wherever. Based on the result of the research, optics based M-Learning had been successfully designed and useful for students in learning process.Kata kunci: bahan ajar optik, mobile learning